Peningkatan Literasi Kewarganegaraan dan Kesadaran Multikulturalisme pada Masyarakat Papua Selatan - Arin Mantara Anggawirya; Rosalia Floriani; Survey Sijabat; Nurul Istiqomah; Evelin Giovani; Rival Hanip (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Civic literacy is something that comes along with civic learning in formal education, but this limits people's understanding of how to implement their civic engagement in society. This community service focuses on two main things, namely, civic literacy and also multicultural awareness. This service activity was carried out on the South Papuan community involved in various youth organizations as many as 24 people consisting of various demographic representations. The results of this service show a change in behavior patterns and perceptions presented in the results and discussion section.